Religious conversion among the Dalit community in Resunga municipality: Push factors from hinduism to christianity - Kunwar, Ramesh Jang (Nepal Sociological Journal, 2025)
This research investigates the factors behind religious conversion from Hinduism to Christianity within the Dalit community in Resunga Municipality located in Gulmi, Nepal. This research specifically targets four wards of the municipality (ward No. 1, 2, 8, and 9), where three churches are established with a notable Dalit population. The research identifies the primary factors for conversion as dissatisfaction with the norms and values of Hinduism, idol worshiping (Murti Puja), the animal sacrifice system, showy culture, false stories, and the influence of specific castes, inability to understand, and lack of clarity regarding eternal life. The discriminatory cultural norms and values embedded in Hinduism, such as the dominance of higher castes and the prohibition of Dalit participation in religious activities, are significant factors for conversion. Specifically, the Dalit respondents expressed dissatisfaction with the hierarchical caste system, which marginalized and oppressed them, due to a desire for social equality and justice. The prohibition of Dalit access to temples, along with the focus on idol worship and the culture surrounding religious events, further contributed to their disapproval of Hinduism. Furthermore, the influence of Christian missionaries, who emphasized the accessibility of God through prayer rather than animal sacrifice, played a vital role in promoting alternative beliefs among the Dalit community. More factors, such as the lack of truth and credibility in Hindu religious texts, along with the inability to comprehend Sanskrit scriptures, lead to conversion. Furthermore, the influence of specific castes in politics and power, and the absence of a clear concept of eternal life, were major factors behind conversion. Despite the presence of anti-conversion laws, the number of Christians in the Dalit community continues to rise. The findings of this research shed light on the factors influencing religious conversion and highlight the Dalits’ quest for equality, inclusivity, and a fulfilling spiritual experience in their transition from Hinduism to Christianity.